Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/tr-06-2020-0257
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of health risk perceptions in tourism, following the COVID-19 pandemic

Abstract: Purpose The purpose of this paper is to clarify the concept of perceived risks, identify the main antecedents and outcomes of health risk perceptions and propose a conceptual model of health risk perceptions in tourism. Design/methodology/approach This paper provides a review of the literature on customer risk perceptions, along with their antecedents and outcomes, and proposes a conceptual model of health risk perceptions in tourism. Findings Key findings reveal that the main factors of health risk percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 90 publications
(127 reference statements)
5
85
0
9
Order By: Relevance
“…Tourism activities make use of the natural landscape as well as the ecological and human–social resources to improve the physical and mental health of the participants through human planning [ 26 ]. However, the current epidemic is still unclear, and the side effects and uncertainties arising from the external risks of travel, man-made hazards, and factors such as the epidemic and climate change will increase the risk of travel and affect people’s willingness to travel [ 27 ]. Therefore, this study assumed that the awareness of environmental risks in travel can be used to estimate people’s willingness to travel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourism activities make use of the natural landscape as well as the ecological and human–social resources to improve the physical and mental health of the participants through human planning [ 26 ]. However, the current epidemic is still unclear, and the side effects and uncertainties arising from the external risks of travel, man-made hazards, and factors such as the epidemic and climate change will increase the risk of travel and affect people’s willingness to travel [ 27 ]. Therefore, this study assumed that the awareness of environmental risks in travel can be used to estimate people’s willingness to travel.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to understand people’s perceptions of policies in order to obtain more in-depth answers [ 38 , 39 ]. Currently, there have been many studies on policy-making and environmental risk perceptions [ 35 , 36 , 37 , 38 ], and a number of studies on physical and mental health perceptions [ 37 , 40 ], as well as health beliefs [ 27 ]. Although there are studies related to decision making, environmental risks and travel intentions [ 41 , 42 ], there are not many studies focusing on policy-making and environmental risk cognition, health beliefs, and physical and mental health cognition related to travel intentions for international travel during an epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its public health impacts COVID-19 has restructured the landscape for business operations with many businesses closed on a permanent or temporary basis (Bartik, 2020). Tourists perceptions of risk associated with the spread of the pandemic have resulted in changing patterns of mobilities and radical shifts in patterns of consumer demand to which businesses have to adapt (Korinth, 2020;Kowalska and Niezgoda, 2020;Neuburger and Egger, 2020;Sánchez-Cañizares et al, 2020;Godovykh et al, 2021;Rogerson and Rogerson, 2021a). Seemingly, the ways that tourism businesses are confronting and responding to the debilitating effects of the COVID-19 pandemic vary geographically across different regions of the world as is shown by the eight country study undertaken by Alonso et al (2021aAlonso et al ( , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…We should think about investing in new strategies to activate the tourism and air sector, when surveys show that tourists do not want to travel and are afraid of getting infected on airplanes and public transport (Figure 5). According to Hasan et al (2017) and Godovykh et al (2021) suggest that a negative correlation between risk perceptions and tourists’ behavioral intentions. It was reported that higher levels of perceived risk evaluations led to lower levels of satisfaction, loyalty, attitude toward a destination and visit intentions.…”
Section: Results Of Researchmentioning
confidence: 99%